Assessment of the impact of land-use management and biodiversity conservation within and adjacent to the Magalies mountain ridge, in Mamelodi (Tshwane), South Africa - Acher, Emma (University of Pretoria, 2022)
Dissertation (MSc (Environment and Society))--University of Pretoria, 2022.